IMPLEMENTASI PENANGANAN SERANGAN MAC-CLONE PADA HOTSPOT MIKROTIK DI STMIK PRADNYA PARAMITA MALANG (STUDI KASUS: STMIK PRADNYA PARAMITAMALANG) - Dwi Ratnasari, Santi; Safiroh Utsalina, Dwi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
One of the facilities that is needed is a network agency. In educational institutions such as Colleges and universities are needed to look for references as well as add insight. The technology used is one that is technology hotspot. Currently there are many hotspot technology is applied to the High School and College. However, the hotspot network mikrotik used in STMIK Pradnya Paramita Malang still experienced many problems in network security. Attacks are frequent and intrusive security network that attacks Mac Clone. Disrupt and complicate the issue of employees as well as students who have access rights legally due access rights are duplicated by users who are not responsible. Therefore, to overcome these problems built a network security by firewall settings that the filter rule and NAT. Based on test results concluded that in building a network security RouterOS hotspot using 5.18 to leave the setting on the firewall, can address the existing Mac Clone attack on STMIK Pradnya Paramita Malang.Â Keywords: Firewall, Hotspot, Mac Clone, Mikrotik RouterOS 5.18.